An experimental characterization of core turbulence regimes in Wendelstein 7-X. (2nd August 2021) - Carralero, D.; Estrada, T.; Maragkoudakis, E.; Windisch, T.; Alonso, J.A.; Beurskens, M.; Bozhenkov, S.; Calvo, I.; Damm, H.; Ford, O.; Fuchert, G.; García-Regaña, J.M.; et al.
Abstract: First results from the optimized helias Wendelstein 7-X stellarator (W7-X) have shown that core transport is no longer mostly neoclassical, as is the case in previous kinds of stellarators. Instead, power balance analysis has shown that turbulent transport poses a serious limitation to the global performance of the machine. Several studies have found this particularly relevant for ion transport, with core ion temperatures becoming clamped at relatively low values of T i ≃ 1.7 keV, except in the few scenarios in which turbulence can be suppressed. In order to understand the precise turbulent mechanisms at play and thus design improved performance scenarios, it is important to have a clear understanding of the parametric dependencies of turbulent fluctuations, and the relation between them and turbulent transport. As a first step in this direction, in this work we use Doppler reflectometry measurements carried out during a number of relevant operational scenarios to provide a systematic characterization of ion-scale ( k ⊥ ρ i ≃ 1) density fluctuations in the core of W7-X. Then, we study the relation between fluctuation amplitude and plasma profiles and show how distinct regimes can be defined for the former, depending on normalized gradients a / L n and a / L T i . Furthermore, we discuss the importance of other potentially relevant parameters such as T e / T i, E r or collisionality. Comparing the different regimes, we find that turbulence amplitude depends generally on the gradient ratio η i = L n / L T i, as would be expected for ITG modes, with the exception of a range of discharges, for which turbulence suppression may be better explained by an ITG to TEM transition triggered by a drop in collisionality. Finally, we show a number of scenarios under which T i, core > 1.7 keV is achieved and how core fluctuations are suppressed in all of them, thus providing experimental evidence of microturbulence being the main responsible for the limited ion confinement in W7-X.